Standardizing Medical Information: Health Level Seven. - Fauman, Michael A. (Psychiatric Times, 2003)
Presents information on Health Level Seven, a protocol developed by information technologists for the U.S. health care information systems. Prevalence of data incompatibilities in health care organizations; Processes involved in the protocol; Discussion on object-oriented programming, a software where the protocol is based.